(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
An innovative way of teaching languages, task-based language teaching (TBLT) emphasises the use of real-world tasks to help students learn. The incorporation of TBLT into financial education is examined in this article, which also shows how its tenets can be successfully implemented to enhance classroom instruction and raise student achievement. Teachers can design interesting and meaningful learning experiences that promote financial literacy and efficient financial management by putting an emphasis on authenticity, task complexity, learner-centeredness, communication, integration, cooperation, and assessment. The goal of the article is to give educators a thorough framework for rethinking their methods of instruction and better preparing their pupils for the needs of the financial sector